Brachytherapy in treatment of coronary heart disease - Mucha, Anna; Nowicka, Elżbieta; Składowski, Krzysztof (Contemporary Oncology/Współczesna Onkologia, 1999)
Restenosis – recurrent stenosis of coronary heart comprise 40% of failures of percutaneous transluminal coronary angioplasty (PTCA). The rationale for use of ionizing radiation in prevention of restenosis is based on the biological and cellular mechanisms of restenosis. Intravascular brachytherapy is a new field of radiotherapy indicationed for this non-malignant disease. It allows administration of high dose of radiation in precise area of narrowed artery. The aim of present work is to describe patomechanism of restenosis and to analise references of laboratory and clinical trials with the use of brachytherapy in treatement of coronary heart disease.